Pengaruh Knowledge Sharing Terhadap Kinerja Karyawan (Studi Kasus Pada UMKM Teknik Logam Jaya) - Khoirusshodiqin, Lutfi Imam (PT Wim Solusi Prima, 2024)
The increasing intensity of business competition demands various companies to devise strategies for their businesses to continue growing. UMKM Teknik Logam Jaya is a company engaged in the metal craft industry, specializing in miniature replica production located in the Pati Regency. Currently, the company is experiencing instability in meeting targets due to issues related to quality, production quantity, and employee performance. This research aims to analyze and understand the impact of knowledge sharing on employee performance at UMKM Teknik Logam Jaya. The population in this study consists of the total number of employees at UMKM Teknik Logam Jaya working in the miniature replica production department, totaling 10 employees, and the sample used includes the entire population. Data for this research were collected using a questionnaire distributed to employees at UMKM Teknik Logam Jaya. The analysis technique used is simple linear regression using the IBM SPSS 22 software tool. The results of the data analysis in this study indicate a positive and significant hypothesis test. This means that knowledge sharing has a positive and significant effect on employee performance.